Romances of the Archive in Contemporary British Fiction. - Keen, Suzanne (University of Toronto Press, 2001)
A detailed examination of the growing genre of British fiction featuring archives and archival research, from A.S. Byatt's Booker Prize-winning Possession to the paperback thrillers of popular novelists.